2010
DOI: 10.1007/s10705-010-9414-0
|View full text |Cite
|
Sign up to set email alerts
|

Managing soil fertility diversity to enhance resource use efficiencies in smallholder farming systems: a case from Murewa District, Zimbabwe

Abstract: Smallholder farms in sub-Saharan African exhibit substantial heterogeneity in soil fertility, and nutrient resource allocation strategies that address this variability are required to increase nutrient use efficiencies. We applied the Field-scale resource Interactions, use Efficiencies and Long-term soil fertility Development (FIELD) model to explore consequences of various manure and fertilizer application strategies on crop productivity and soil organic carbon (SOC) dynamics on farms varying in resource endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 24 publications
4
48
0
Order By: Relevance
“…Both lower midland zones had higher crop diversity since farmers sought to maintain diverse crops to mitigate against various uncertainties, especially unpredictable climatic conditions. The crop diversity found represented a high level of species richness which is supported by other studies on agrobiodiversity [33]. Overall (all zones) 38 25 13 The current study recorded low diversity in TUM although the region is on the slope of Mt.…”
Section: Agrobiodiversity In Smallholder Farmssupporting
confidence: 84%
See 1 more Smart Citation
“…Both lower midland zones had higher crop diversity since farmers sought to maintain diverse crops to mitigate against various uncertainties, especially unpredictable climatic conditions. The crop diversity found represented a high level of species richness which is supported by other studies on agrobiodiversity [33]. Overall (all zones) 38 25 13 The current study recorded low diversity in TUM although the region is on the slope of Mt.…”
Section: Agrobiodiversity In Smallholder Farmssupporting
confidence: 84%
“…The household heads were the sole decision makers regarding crops grown where elderly people had high preference for indigenous crops for nutritional and medicinal purposes [24]. Zingore et al [33] recorded similar results in Zimbabwe where elderly smallholder farmers put more emphasis on traditional crop varieties.…”
Section: Agrobiodiversity Contribution To Food Securitymentioning
confidence: 91%
“…In contrast to earlier findings, however, there was no meaningful correlation between farm size and the attitudes of farmers toward organic farming. Studies such as Zingore et al [37], Cukur [13], Karki et al [20], Oluwasusi [11], Adebayo and Oladele [34], and Chouichom and Yamao [30] showed a positive correlation, and other studies, for example, Alzaidi et al [22] and Khaledi et al [32], reported a negative correlation between the attitude toward organic farming and farm size.…”
Section: Resultsmentioning
confidence: 99%
“…Income is associated with the amount of owned land as it is one of the resources for agricultural production. According to Zingore et al [37], wealthier farmers own more land. Some studies such as Oluwasusi [11], Cukur [13], Karki et al [20], Chouichom and Yamao [30], and Adebayo and Oladele [34] show that the attitude toward organic farming has a positive correlation with farm size.…”
mentioning
confidence: 99%
“…Extensive research has been conducted into the broader frameworks of integrated soil fertility management [130][131][132][133][134][135][136][137], conservation agriculture [138][139][140][141][142][143], erosion control [144][145][146][147][148], and improved grazing management [149][150][151]. There is also a wealth of information on the benefits of specific practices such as short legume rotations (improved fallows) [152][153][154][155][156][157][158], agroforestry systems [159][160][161][162][163][164][165], and no-till systems [166][167][168][169][170].…”
Section: Positive Trajectories and Conclusionmentioning
confidence: 99%